Pemberian Penyuluhan Kesehatan Mengenai Stunting Pada Pemuda Pemudi di Dusun II Pekik Nyaring, Kec. Pondok Kelapa, Kab. Bengkulu Tengah - Khairunnisa, Miska; Utomo, Meto Widio; Wilantara, Anggi (LPPM Universitas Dehasen Bengkulu, 2024)
Stunting is a disruption in the growth and development of children due to long-term malnutrition. Stunting can be caused by malnutrition experienced by the mother during pregnancy, or by the child during his growth period.